2021
DOI: 10.2147/ijgm.s326767
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Perception Among Saudi Arabian Population About Resharing of Information on Social Media Regarding Natural Remedies as Protective Measures Against COVID-19

Abstract: Introduction: Ever since COVID-19 was declared as a global pandemic, there has been a prevalence of misinformation circulating online on social media platforms. In order to better tackle COVID-19 it is important to determine how the general population perceive the sharing of medical information on social media platforms. Based on this, the aim of the study is to analyse the perception of Saudi Arabian Health Care Workers' (HCWs) and Non-Health Care Workers' (NHCWs) regarding the sharing and resharing of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…A national cross-sectional study found that the most reported information sources about the COVID-19 crisis were the internet/social media (85.8%), health practitioners (54.7%), TV/Radio (35.7%), family/friends (29.5%), and other sources (7%) [57] . Similarly, the most widespread social media platforms used among HCWs and non-HCWs during the early stages of the pandemic in KSA were WhatsApp (51.6%), Twitter (27.6%) and Snapchat (13.8%) [58] . Other commonly reported information sources used among HCWs are health care providers and the World Health Organization (WHO) [59] , as well as hospital announcements, MOH official statements among other sources [60] .…”
Section: Discussionmentioning
confidence: 99%
“…A national cross-sectional study found that the most reported information sources about the COVID-19 crisis were the internet/social media (85.8%), health practitioners (54.7%), TV/Radio (35.7%), family/friends (29.5%), and other sources (7%) [57] . Similarly, the most widespread social media platforms used among HCWs and non-HCWs during the early stages of the pandemic in KSA were WhatsApp (51.6%), Twitter (27.6%) and Snapchat (13.8%) [58] . Other commonly reported information sources used among HCWs are health care providers and the World Health Organization (WHO) [59] , as well as hospital announcements, MOH official statements among other sources [60] .…”
Section: Discussionmentioning
confidence: 99%
“…In Singapore, most Internet users ignore the FNI they come across and only offer corrections when the issue is strongly relevant to them and to people with whom they share strong and close interpersonal relationships (Tandoc et al, 2020). Globally, Saudi Arabia has a comparatively higher level of awareness and higher reluctance to share medical information related to coronavirus disease 2019 (COVID-19) INTR 32,5 online (Alshareef and Alotiby, 2021). Mobile connectivity and political freedom in a nation contribute to COVID-19-related FNI propensity, whereas economic and media freedom inhibit it (Shirish et al, 2021).…”
Section: Input Of Fnimentioning
confidence: 99%
“…, 2020). Globally, Saudi Arabia has a comparatively higher level of awareness and higher reluctance to share medical information related to coronavirus disease 2019 (COVID-19) online (Alshareef and Alotiby, 2021). Mobile connectivity and political freedom in a nation contribute to COVID-19-related FNI propensity, whereas economic and media freedom inhibit it (Shirish et al.…”
Section: Literature Analysismentioning
confidence: 99%
“…15 Alshareef and Alotiby found that Saudi people accept sharing health information without evidence on social media, believing that sharing is harmless, although they were aware of their unreliability. 16 WhatsApp was the most preferred social media platform. 16 In Arabic-speaking communities, research on the validity/safety and credibility of WhatsApp health information is scarce.…”
Section: Introductionmentioning
confidence: 99%